From Idea to Innovation: Unveiling the Design-Based Research Experiences in a State University - Gamboa, Alberto G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Design-based research is a methodology that integrates theory and practice to develop innovative solutions in re-al-world educational settings. This study employed a phe-nomenological approach, intended to understand the lived ex-periences design-based researchers towards their research undertakings from January to May 2024. It aimed to describe the experiences of design-based researchers in conducting DBR: challenges encountered, strategies employed in address-ing the challenges, and insights gained. Twenty purposively sampled participants were interviewed using a validated open-ended questionnaire. The data were analyzed through reflexive thematic analysis. Where, the research revealed that de-sign-based researchers experience a mix of fulfillment and challenges, including a lack of prior experience, time constraints, stress, financial limitations, and interper-sonal conflicts. To navigate these hurdles, they employ strategies such as maintaining a proactive mindset, col-laborating with stakeholders, and embracing flexibility and continuous learning. The study emphasizes the need for collaborative networks and mentorship while rec-ommending enhanced support through training and re-sources to improve the DBR research process and out-comes.